The Introduction of the Fourth Estate into Malaysian Jurisprudence and its Impact on Political Libel: A Prefatory View - Sadhu Singh, Jaspal Kaur (Journal of Malaysian and Comparative Law, 2018)
The paper considers the impact of the Court of Appeal decision in Utusan Melayu (Malaysia) Berhad v Dato’ Sri DiRaja Haji Adnan bin Haji Yaakob on the role of the media as the Fourth Estate. It focuses on the determination by the court that a political libel suit against a newspaper will result in inhibiting free speech that is in the public interest such as a critique against democratically elected bodies or individuals. This paper argues that firstly, by the court taking the position as laid down in the House of Lords’ decision of Derbyshire CC v Times Newspapers Ltd, the court introduces the role of the media acting as a Fourth Estate into Malaysian jurisprudence, and secondly, building on the said position, prohibiting a political libel suit being taken by an individual against a media entity. It is contended that there is a foundational basis that by prohibiting a political libel action against a media entity, the court has endorsed this role as being vital in the functioning of a democracy. The paper sets out, firstly, an in-depth understanding of the role of the media as the Fourth Estate, the theoretical underpinnings and the underlying legal rationale, in particular the protection of freedom of speech and expression, for the justification of the said role. Secondly, the paper describes the proposition in Derbyshire and its extrapolation into Malaysian common law in Utusan Melayu. Thirdly, it establishes a nexus between the judgments in Derbyshire and Utusan Melayu that the media’s role to check on government is a dimension of freedom of speech and expression that should not be suppressed or curtailed, particularly by defamation suits against media entities that are viewed as stifling this role. Finally, the author reflects on several post-judgment considerations drawn from both judgments.